2009
DOI: 10.1037/a0015811
|View full text |Cite
|
Sign up to set email alerts
|

Parent–child role reversal and psychological adjustment among immigrant youth in Israel.

Abstract: Parent-child role reversal and its relation to psychological adjustment was investigated in Israel among immigrants from the former Soviet Union. Study 1 examined immigrant and Israeli-born college students (n = 184), and Study 2 examined adolescents (n = 180) by means of self-report questionnaires. Two major factors of role reversal emerged: child dominance and family support. The results of both studies clearly showed that immigrants assume more dominant roles and parental responsibilities in their families … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 49 publications
5
72
0
5
Order By: Relevance
“…Ample evidence supports this association in the case of FSU immigrant adolescents: family support, the quality of relationships with parents and of family functioning -have been found to be associated with normative adjustment among FSU immigrant adolescents (Elitzur et al, 2007;Mesch et al, 2008;Oznobishin & Kurman, 2009;Slonim-Nevo et al, 2009;Sagy et al, 2009;Dwairy & Dor, 2009) Family support is not guaranteed in migration as familial crises and decline in parental functioning are a common phenomenon. Numerous factors may negatively affect parental functioning in migration.…”
Section: Family and Parental Supportmentioning
confidence: 96%
See 1 more Smart Citation
“…Ample evidence supports this association in the case of FSU immigrant adolescents: family support, the quality of relationships with parents and of family functioning -have been found to be associated with normative adjustment among FSU immigrant adolescents (Elitzur et al, 2007;Mesch et al, 2008;Oznobishin & Kurman, 2009;Slonim-Nevo et al, 2009;Sagy et al, 2009;Dwairy & Dor, 2009) Family support is not guaranteed in migration as familial crises and decline in parental functioning are a common phenomenon. Numerous factors may negatively affect parental functioning in migration.…”
Section: Family and Parental Supportmentioning
confidence: 96%
“…Numerous factors may negatively affect parental functioning in migration. The preoccupation with financial problems and their own adjustment difficulties may render parents less available or attentive to their children (Eisikovits & Shamai, 2001;Yakhnich & Ben-Zur, 2008;Oznobishin & Kurman, 2009;Dwairy & Dor, 2009). Single parents may be less capable than parents in full families to provide parental protection and support (Soskolne, 2001).…”
Section: Family and Parental Supportmentioning
confidence: 99%
“…Children's disclosure is not a typical outcome in acculturation research, but it can be assumed to be affected by immigration because research has shown that the parent-child relationship can change with the transition to a new country (Oznobishin and Kurman 2009;Portes 1997;Titzmann 2012). …”
Section: Mother-adolescent Agreement On Child Disclosurementioning
confidence: 99%
“…Family obligations and adolescent mental health were also examined by Oznobishin and Kurman (2009) in terms of role reversal. They compared two cohorts of immigrants from the former Soviet Union with their Israeli-born peers.…”
Section: Parent-adolescent Relationships and Adolescentmentioning
confidence: 99%
“…On the other hand, however, the contributions center on many groups that are only rarely discussed in North American social science journals. For instance, the article by the Portuguese psychologist Neto (2009) reports on the mental health of immigrant adolescents originating in Cape Verde, Angola, India, Mozambique, East Timor, Sao Tomé, and Guinea; two articles by Dwairy and Dor (2009) and Oznobishin and Kurman (2009), respectively, focus on the sometimes difficult adjustment experiences of Russian Jewish immigrants residing in Israel; Merz, Kocabas, Oort, and Schuengel (2009) examine notions of family solidarity among immigrants from Morocco, Suriname, the Dutch Antilles, and Turkey to the Netherlands; Titzmann and Silbereisen (2009) analyze friendship networks among ethnic German immigrant adolescents whose families returned after many years from post-Soviet countries to the land of their ancestors; and Luster et al (2009) It is important to note in this context that the overall social and cultural conditions as well as the emotional climate of acceptance or rejection that host societies offer to their immigrant families and children will exert a major impact on the children's psychosocial adjustment. For example, Neto (2009) reports that Portuguese society traditionally has broadly accepted multiracial and multicultural immigrants, including those arriving from former Portuguese colonies located in Africa, South America, and Asia.…”
mentioning
confidence: 99%